Synthesis and characterization of methylene-xylene-based polysulfide block-copolymer/carbon nanotube nanocomposites via in situ polymerization method. (3rd July 2020) - Sheydaei, Milad; Alinia-Ahandani, Ebrahim
ABSTRACT: Good resistance to the solvent, UV radiation and excellent adhesion to surfaces are the significant features of polysulfide polymers. They are known to have extensive applications as sealants and a variety of coatings. In this work, a polysulfide copolymer was synthesized using linear and aromatic organic monomers (methylene dichloride and α, α ′-dichloro- p -xylene) and sodium tetrasulfide aqueous monomer. Using carbon nanotube (CNT) modified by acid (CNTCOOH), the nanocomposites of poly(methylene-xylene tetrasulfide) (PMXTS) were synthesized via in situ polymerization. The structural characteristics of polysulfide copolymer, modified CNT and nanocomposites were identified by Fourier transform infrared (FTIR) and Raman spectroscopies. Increasingly, morphological and thermal properties of samples are studied using X-ray diffraction (XRD), scanning electron microscopy (SEM), differential scanning calorimetry and thermogravimetric analysis techniques, respectively. Also, the molecular weight of the copolymer was determined by proton nuclear magnetic resonance ( 1 H NMR). The results showed that along increasing CNTCOOHs in the nanocomposites, glass transition temperature occurs at higher temperatures, and melting temperature increased wonderfully, but did not have a significant effect on the degradation temperature. Furthermore, the copolymer is dissolved partially in dimethyl sulfoxide (DMSO) but the presence of CNTCOOHs reduces this solubility. GRAPHICAL ABSTRACT: